Pengaruh Rokok Terhadap Kadar Kolesterol 2 Jam Setelah Merokok Pada Perokok Aktif - Hainun Nisa; Dita Ellyana Artha; Risma risma (Jurnal Media Laboran, 2018)
This study was motivated by the effect of smoking on cholesterol levels 2 hours after smoking in active smokers. By knowing cholesterol levels before smoking and 2 hours after smoking. The method used in this study is colorimetric enzymatic CHOD-PAP which is a method of measuring cholesterol levels in the blood that uses the help of 3 enzymes, namely: cholesterol esterase, cholesterol oxidase and peroxidase.From the results of 10 samples of cholesterol examination conducted at the D-3 Laboratory of Health Analysts at the University of East Indonesia Makassar, and analyzed by t-test it can be concluded that there was no effect of an increase in cholesterol levels on active smokers 2 hours after smoking with t count (-2,675) <ttabel (2,262) at the significance level of 0.05, then H0 is accepted. Based on the conclusions above, it can be suggested for future researchers to be able to examine other lipid levels such as HDL, LDL or triglycerides for active smokers to see the effect of smoking on blood fat levels.